Supply chain disruptions in the fast-moving consumer goods industry - Tazvivinga Kudakwashe; David Pooe (Journal of Transport and Supply Chain Management)
Background: The fast-moving consumer goods (FMCG) industry is a key sector in the South African economy. In this context, designing disruption-management strategies for a robust supply chain has become a critical worldwide issue that is still under-explored in the FMCG industry.